Patient satisfaction with health care facility provided by outpatient department of Dhulikhel community hospital , Kavre. - Gyawali, Bishal (2009)
ABSTRACT: Background: Patient satisfaction regarding healthcare facility in a hospital is now increasingly used as the tool for quality evaluation and improvement. The study reflects the depth of the health care providers and patient relationship and the overall quality of the services. The objective of the study was to identify the level of satisfaction on health care services among patient of OPD through assessing satisfaction towards health workers behavior, assessing perception on quality of health services, examining satisfaction on cost of health services among people of different economic status and finding out satisfaction on waiting time in OPD. Methods: A descriptive cross-sectional study was done using purposive sampling method for selecting patients within OPD of Dhulikhel Community Hospital. Total 138 patients were included in the research study utilizing the structured questionnaires. Quantitative information was collected through the exit interview. Results: It was found that about 91.3 percent of patient were satisfied with the behavior of the staffs. Majority of the respondents said that health worker keep serious concern about their illness. About 96.4 percent of the respondents were happy about health worker's ability to find out their problems. It was seen that 71 percent of the respondents considered registration fee and cost of the diagnostic services in hospital as reasonable. About 87 percent of the clients were satisfied with waiting time to see the doctors. Overall it was found that 35.32 percent of the patients highly satisfied and 64.68 percent of the patients were fairly satisfied with health care facility of OPD. Conclusion: The findings suggest that the patients were fairly satisfied with the overall services provided from the OPD of the hospital. Better staffs and health workers interpersonal skills, facility, infrastructure, quality of care, cost of care have largest effect in improving patient satisfaction at the hospital. Key words: Outpatient, Quality, Reasonable, Satisfaction